Perilaku Petani Bawang Merah Dalam Penggunaan Pestisida Dan Dampaknya Terhadap Lingkungan Kabupaten Merauke - Jean Laurina Masatuneko (AGRICOLA, 2019)
Excessive use of pesticides will increase the cost of control, heighten the death of organisms and canreduce environmental quality. This study aims to analyze the behavior of shallots farmers in the use ofpesticides and their impact on the environment. The research method used in sampling is usingquantitative methods and qualitative methods. Data collection techniques are done by (1) primarydata, namely through observation, interviews and questionnaires. (2) secondary data, namely throughevidence, records or reports. The results of the increase in farmers' knowledge will be more effectivewith farmers participating in and following the meeting activities held by the Government Institutionon shallot cultivation, so farmers will better understand how to use pesticides and understand itself thedanger of using pesticides for consumers and the environment. The attitude of farmers in the use ofpesticides that are registered, permitted and not expired is not according to the rules because they arereasonable, which can still be used as long as the packaging is not damaged due to pesticides that canincrease production levels. The actions of farmers using personal protective equipment are good butthere are still many farmers who use long-sleeved clothes and shorts on the grounds that farmers donot know the correct function of protective clothing as a whole